Effect of Telang Flower Infusion on Lymphocyte Cells and Neutrophil Cells (Segment And Band) in Microplastic-Induced Rats - Muflihah, Ahdiah Imroatul; Destiawan, Rian Anggia; Sari, Leny Yulia Widia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2026)
Background: Microplastics causing tissue damage and increasing the number of lymphocyte cells and neutrophils (segment and band). Telang flower infusion contains flavonoids as antioxidants that can as immunomodulatory. The purpose of this study was to determine the effect of telang flower infusion on the number of lymphocyte cells, band and segment neutrophils. Methods: Methode begins with the manufacture of telang flower infusion, the manufacture of microplastics (heating bottled drinking water at a temperature of 65oC), the analysis of the size of microplastics using electron microscopes, the analysis of microplastic types using the FTIR method, the grouping of negative control, positive control, and treatment with a dose of 4 ml/250g BW, exposure to microplastics, blood smear, giemsa staining for lymphocyte and neutrophil cell analysis, and statistical test using One-Way ANOVA (p<0.05) with Tuckey HSD (p<0.05). Results: The results showed that the average number of negative control band neutrophil cells (3.50+4.50), positive control (3.17+3.81), and treatment (5.33+3.61) and the One-Way ANOVA analysis showed values (p=0.81>p=0.05), the average segment neutrophil cells of the negative control (23.67+6.80), the positive control (21.33+5.82), the treatment (24.00+8.19), and the One-Way ANOVA analysis showed values (p=0.776>p=0.05), negative control lymphocyte cells (68.50+14.84), positive control (72.17+4.99), and treatment (64.00+12.10). The One-Way ANOVA analysis showed a value of (p=0.481>p=0.05). Conclusions: It can be concluded that telang flower infusion has a tendency to act as an immunomodulator at the biological level characterized by a decrease in lymphocyte cells, an increase in band neutrophil cells and segment nuetrophic cells.